Gender Differences in Mathematics Anxiety Among Preservice Teachers and Perceptions of Their Elementary and Secondary School Experience with Mathematics - Bowd, Alan D.; Brady, Patrick H. (Alberta Journal of Educational Research, 2003)
This study investigated experiential antecedents of mathematics anxiety and associations with gender among preservice student teachers. Participants were 357 students enrolled in the final year of a teacher education program. They responded to the Mathematics Anxiety Rating Scale (Richardson & Suinn, 1972) and a questionnaire to assess experience with mathematics in the elementary and secondary school together with attitudes toward mathematics and beliefs about the subject. Male and female participants did not differ informal mathematics achievement or the time elapsed since taking a mathematics course. Several gender differences were found in perceptions of school mathematics experience, and both men and women reported greater enjoyment of mathematics in elementary school compared with high school. Women expressed less positive beliefs about their use of, and intrinsic interest in, mathematics. Associations between mathematics anxiety and both perceptions of school experience and beliefs about mathematics were higher for women. Negative experience with mathematics in high school was an important precursor of mathematics anxiety, especially among women. Some implications for teacher education programs were reviewed; these emphasize the importance of both teachers' and peers' behavior, especially in the high school environment.